Advanced composites based on end-capped polyarylene ether nitrile/bisphthalonitrile with controllable thermal curing reaction. (6th April 2022) - He, Liang; Tong, Lifen; Xia, Yunqing; Lin, Guo; Wang, Ting; Zhang, Wanru; Liu, Yingfa; Liu, Xiaobo
Abstract: A novel polymer was prepared through the combination of phthalonitrile end-capped polyarylene ether nitrile (PEN-Ph) and bisphthalonitrile (BPh), applying post-solid phase chemical reaction technology. BPh monomer was firstly pre-polymerized to form BPh prepolymer and then followed by crosslinking reaction with PEN-Ph matrix resin to obtain PEN-Ph/BPh composites. The generated crosslinking structures were confirmed by FTIR and UV including phthalocyanine, triazine, and isoindoline rings. Besides, the effect of BPh pre-polymerization time on the performance of PEN-Ph/BPh composite materials was studied. Tensile s trength and modulus highest values of composites exceeded 98.9 MPa and 2.17 GPa respectively as BPh pre-polymerization time reached 30 min, improved by 55.6% and 36.9% in comparison with unpolymerized one. Besides, PEN-Ph/BPh composite films exhibited superior thermal properties ( T g : 278–330 °C, T 5% (decomposition temperature of 5 wt%)>500 °C) and maintained excellent dielectric stability over 300 °C, leading to use for electronic fields at elevated temperature. Graphical abstract: Image 1 Highlights: BPh is firstly applied as a novel crosslinking agent to reinforce PEN-Ph. The crosslinking density of PEN-Ph/BPh was controlled by the BPh pre-polymerization. The mechanical performance of PEN-Ph/BPh is sharply improved after modification. The thermal property of PEN-Ph/BPh show significant improvement after modification.